2009
DOI: 10.2139/ssrn.1618142
|View full text |Cite
|
Sign up to set email alerts
|

Remittances and Household Welfare: A Case Study of Bangladesh

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 4 publications
9
54
1
1
Order By: Relevance
“…The result is in line with McKenzie and Rapoport [27] Antman [28], Lee and Park [29] and Mansoor and Quillin [30]. At the same time, the result violates the result of Abbas et al [42] and Raihan et al [43].…”
Section: Impact Of Remittances On Educationsupporting
confidence: 85%
See 1 more Smart Citation
“…The result is in line with McKenzie and Rapoport [27] Antman [28], Lee and Park [29] and Mansoor and Quillin [30]. At the same time, the result violates the result of Abbas et al [42] and Raihan et al [43].…”
Section: Impact Of Remittances On Educationsupporting
confidence: 85%
“…To estimate the extent, household expenditure on education and healthcare purpose is considered as dependent variable. As the dependent variable is continuous, the study applies a multiple regression model estimated through OLS method which shows a cause and effect relationship between dependent variable and a set of explanatory variables following Abbas et al [42], Raihan et al [43] Banik and Kumar [44] and Kumar [45]. Equation 1 states the relationship as follows:…”
Section: Multiple Regression Analysismentioning
confidence: 99%
“…Besides reducing poverty, international remittances enhance the welfare of remittance recipient households. Some previous studies have found a positive relation between remittances and welfare [15,20,[28][29][30]. They found that remittance recipient households spend most amount of remittance received on consumption purposes.…”
Section: Source: World Development Indicatormentioning
confidence: 93%
“…Abbas et al conducted a primary data based study using a binary logistic regression model where they found that one unit increase in remittance receipt decreases the log odds of poverty by 10.6 percent [15]. Some previous studies have also found that remittance reduces poverty significantly [20][21][22][23][24].…”
Section: Source: World Development Indicatormentioning
confidence: 99%
“…Tabuga (2007) en su estudio de Filipinas, encontró que los gastos en salud entre otros se ven incrementados por los flujos de remesas. En el estudio Raihan et al (2009) de Bangladesh, el efecto de las remesas en salud y educación es positivo pero insignificante. En un estudio general en México, Airola (2007) por medio de la enigh de 1984 al 2000, encontró el aumento de los gastos de salud como consecuencia de las remesas.…”
Section: Introductionunclassified